Enhancing the thermosiphon-driven discharge of a latent heat thermal storage system used in a personal cooling device. (April 2018) - Dhumane, Rohit; Mallow, Anne; Qiao, Yiyuan; Gluesenkamp, Kyle R.; Graham, Samuel; Ling, Jiazhen; Radermacher, Reinhard
Highlights: Describes working of a novel personal conditioning device called Roving Comforter. Modelica model developed to simulate the solidification of its thermal storage. Graphite enhancement options for improvement of solidification time analyzed. Potential improvement from graphite enhancement discussed. Abstract: Personal cooling devices reduce energy loads by allowing buildings to operate with elevated setpoint temperatures, without compromising on the occupant comfort. One such novel technology called the Roving Comforter (RoCo) uses a compact R134a based vapor compression system for cooling. Following its cooling operation, during which waste heat from the condensing refrigerant is stored in a phase change material (PCM), a two-phase loop thermosiphon is used to discharge (solidify) the PCM to enable its next operation. The transient operation of this thermosiphon is the focus of the present article. Use of a PCM as the storage medium provides high energy density due to the ability to store thermal energy as latent heat during the phase transition; however, the discharge rate is limited by the low thermal conductivity of the PCM. Insertion of a graphite foam within the PCM can increase the rate of discharge and decrease the downtime of the cooling device. Since graphite enhancement involves a tradeoff between improving the discharge time at the expense of PCM volumetric latent heat, the impact of graphite foam density on the PCM discharge rate is investigated by using a Modelica-based transient model of the thermosiphon. The semi-empirical model, which uses relevant heat transfer coefficient and pressure drop correlations for both refrigerant and airside heat transfer, captures the complex phenomena involving simultaneous phase change of the refrigerant and the PCM. The graphite enhanced PCM selected from this analysis results in a 51% reduction in the discharge time with addition of only 5% to the thermal storage weight, without compromising the required cooling time.